Relations between Church and State in Gaudium et Spes = Les relations Église - État dans Gaudium et Spes = I rapporti tra Chiesa e stato nella Gaudium et Spes - Sitarz, Mirosław (Philosophy & canon law, 2016)
The Second Vatican Council in the Pastoral Constitution on the Church in theModern World Gaudium et Spes concluded teaching relating to ecclesiastical public law. TheCouncil, in a new way, read out the relations between the Church and the political community, defining the basic principles on which these two different types of communities should arrange their mutual relations. In the center of these references has been the human with his/her adherent and inalienable dignity that is the source of all rights and freedom. For this reason, the Council described the catalog of principles in accordance with which they are to be laid the Church–state relations. Among the four principles, the principle of respect for pluralistic society was not mentioned directly in Gaudium et Spes, but taking into account the nature of the Church and the history of mutual relations between her and the state, this principle should be considered as a point of departure for the directly indicated by the Council: religious freedom, autonomy and independence of Church and state and the mutual cooperation between them.